2020
DOI: 10.1016/j.artd.2020.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Common Peroneal Nerve Injury and Recovery after Total Knee Arthroplasty: A Systematic Review

Abstract: Background: Common peroneal nerve palsy (CPNP) after total knee arthroplasty (TKA) may impact extremity pain and function. Incidence and rates of recovery of CPNP after TKA vary in the current literature. The purpose of this systematic review was to evaluate the incidence of incomplete and complete CPNP after TKA and rates of incomplete and complete recovery of nerve function in the absence of further surgical treatment. Methods: PubMed, Embase, and Cochrane Central were searched for studies published in the y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 23 publications
(121 reference statements)
2
26
0
1
Order By: Relevance
“…The obtained overall CPNP ratio of 1.9% in this study falls within the known range of TKA-V (0.3% - 9.5%) [ 3 , 9 – 17 ]. Other systematic review reported a range of 0.01% to 4.3%, like the one of Carender et al [ 2 ] and Rodríguez-Merchán et al [ 50 ]. Currently, controversy still exists related to valgus deformity being a predisposing factor of CPNP.…”
Section: Discussionmentioning
confidence: 99%
“…The obtained overall CPNP ratio of 1.9% in this study falls within the known range of TKA-V (0.3% - 9.5%) [ 3 , 9 – 17 ]. Other systematic review reported a range of 0.01% to 4.3%, like the one of Carender et al [ 2 ] and Rodríguez-Merchán et al [ 50 ]. Currently, controversy still exists related to valgus deformity being a predisposing factor of CPNP.…”
Section: Discussionmentioning
confidence: 99%
“…Common peroneal nerve (CPN) palsy in post-TKR is relatively rare, estimating around 0.4% that too is more common in Rheumatoid and valgus knees. 19,20 We had also one lady with Rheumatoid and valgus knee where we performed simultaneous bilateral total knee arthroplasty in a single setting but she suffered from CPN palsy postoperatively in the left knee that recovered completely after 3 months of physiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…К факторам риска относят травмы голени и колена, ортопедические операции на малоберцовой и большеберцовой костях и поведенческие причины, такие как длительное поддержание позы со скрещенными ногами, сидение на корточках, быстрое снижение массы тела [3]. Травматическое повреждение малоберцового нерва при остео томиях большеберцовой кости в сочетании с остео томией малоберцовой кости описано в 2-27 % случаев, при травмах голени частота таких повреждений может достигать 16-40 %, при эндопротезировании коленного сустава -около 0,4 % [4,5]. К факторам риска развития послеоперационной нейропатии относят использование эпидуральной анестезии, наличие сгибательных контрактур, более высокий индекс массы тела и сахарный диабет в анамнезе [6][7][8].…”
Section: O N T a C T Sunclassified